2009
DOI: 10.1002/macp.200900289
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystals Embedded in Polymeric Electrolytes for Quasi‐Solid State Dye‐Sensitized Solar Cell Applications

Abstract: A new series of liquid crystal embedded in polymeric electrolytes was developed for obtaining high efficiency in quasi‐solid state dye‐sensitized solar cells (DSSCs). The polymeric electrolytes were composed of iodide and tri‐iodide redox species in polyacrylonitrile (PAN) as a polymer matrix and liquid crystals (E7 or ML‐0249) for increasing the order parameter of electrolyte components with easy transport of redox species. The highest efficiency (6.21 and 6.29% at 1 sun) was obtained for the quasi‐solid stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
0
30
1
Order By: Relevance
“…As shown in Table 2, the doped LCs increases R ct and consequently decreases J SC and PCE of the DSSCs. However, these results are inconsistent with those in the literature [22,23], which claim that the addition of LCs generally increases the PCE of the polymer electrolyte-based DSSCs because the doped LCs increase the additional conductive pathways of the polymer electrolyte [23,35]. The main reason is that the massive LC dopant change the order parameter of the polymer electrolyte.…”
Section: Resultscontrasting
confidence: 67%
“…As shown in Table 2, the doped LCs increases R ct and consequently decreases J SC and PCE of the DSSCs. However, these results are inconsistent with those in the literature [22,23], which claim that the addition of LCs generally increases the PCE of the polymer electrolyte-based DSSCs because the doped LCs increase the additional conductive pathways of the polymer electrolyte [23,35]. The main reason is that the massive LC dopant change the order parameter of the polymer electrolyte.…”
Section: Resultscontrasting
confidence: 67%
“…developed liquid crystal embedded in polymeric electrolytes were developed for obtaining high efficiency quasi-solid state dye-sensitized solar cells and its performed similarly to liquid electrolyte. The high ionic conductivity of the LC embedded in polymeric electrolyte leads to enhancement in photovoltaic performance [25,26]. Ahn et al developed a polymer electrolyte consisting of poly(vinylidene fluoride-co-hexafluoropropylene) (e-PVdF-co-HFP) gel doped with the LC E7 which resulted in an increase of its PCE in dye-sensitized solar cell (DSSC) application [27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent days, a few studies have shown that the introduction of liquid crystal into the electrolyte for the DSC would enhance the ion conductivity and thus the photovoltaic performance of the DSC [17,18]. Kim et al [19,20] has successfully introduced the liquid crystals E7 and ML-0249 into the polyacrylonitrile (PAN) based polymer electrolyte to improve the ion conductivity and therefore the short-circuit current density of the DSC. However, reports about the application of LC in DSC are still limited.…”
Section: Introductionmentioning
confidence: 99%